Impacto que Genera la Implementación de las NIIF para Pymes - Barrios Narváez, Daniela Alejandra (Universidad Antonio Nariño, 2021)
Colombia adopts the International Financial Reporting Standards IFRS for Smes, seeking to align with international economic, financial, legal and accounting protocols that affect Colombian companies, improve their competitiveness at the international level, facilitate the reading and analysis of their financial statements, contribute to decision making and achieve potential benefits. Determine the financial impact generated by the implementation of IFRS in Smes in Colombia. - Identify the economic, financial and legal impacts of the adoption of the IFRS for Smes on companies in Colombia. - Identify main challenges faced by small and medium-sized companies in Colombia in the process of implementing the IFRS for Smes. Key words: IFRS, Smes, Impact, Challenges, Implementation.